POSITION VECTORS OF ADMISSIBLE CURVES IN 3-DIMENSIONAL PSEUDO-GALILEAN SPACE G31 - Oztekin, Handan; Bozok, Hulya Gun (Int Electronic Journal Geometry, 2015)
In this paper, position vectors of admissible curves in pseudo-Galilean space G(3)(1) is studied in terms of Frenet equations. We compute the position vectors of admissible curves in pseudo-Galilean space G(3)(1). Then we give some examples of position vectors for admissible curves.
Keywords: Pseudo-Galilean space; admissible curve; position vector